Aerobic training as a means to enhance inhibition: what's yet to be studied?. Issue 1 (December 2015) - Levin, Oron; Netz, Yael
Abstract Some of the neurodegenerative processes in healthy aging, including changes in structural and biochemical properties of the brain, are argued to affect cortical inhibitory functions. Age-related deficits in the ability to control cerebral inhibition may explain wide range of motor and cognitive deficits that healthy older adults experience in daily life such as impaired coordination skills and declines in attention, concentration, and learning abilities. Importantly, evidence from many studies suggests that impaired inhibitory control in advancing age can be delayed or even alleviated by aerobic exercise training. Findings from a recent study by Duchesne and colleagues (2015) may provide insights into this process. First, observations from Duchesne et al. indicated that aerobic exercise training program improved cognitive inhibitory functioning in both patients with Parkinson's disease (PD) and matched older controls. Second, Duchesne et al. showed that cognitive inhibition and motor skills were highly correlated both pre- and post-exercise in PD but not in controls. Based on the aforementioned findings we highlight possible mechanisms that may play a role in the interactions between cognitive and motor inhibitory functions in healthy elderly that could benefit from aerobic exercise training: specifically, the brain neurotransmission systems and the frontal-basal ganglia network. In conclusion, we raise two fundamental questions which are yet to be addressed: (1) the extent to which different brain neurotransmitter systems are affected by aerobic exercise training; (2) the extent to which neurotransmitter levels prior to the onset of intervention may facilitate (or impede) training-induced neuroplasticity in the aging brain.